MEKANISME ATAS WAKAF UANG STUDI KASUS PADA KSPPS BMT MANDIRI SEJAHTERA CABANG KRANJI - Siswoyo, Siswoyo; Hidayatul Istiqomah, Nur (Jurnal Perbankan Syariah, 2021)
Abstract: Baitul Maal Wat Tamwil (BMT) as a financial institution in the economic realm This is a breath of fresh air for people who are starting to worry about the many practices of usury in conventional banking, especially in the microeconomic community. Institution. Sharia-based finance can be an alternative for people who avoid financial economy based on usury on conventional financial institutions. BMT is included in cooperative legal entity that is subject to Law no. 25 of 1992 About Cooperatives, PP RI No. 9 of 1995 concerning the Implementation of Savings and Loan Business Activities by cooperatives, Decree of the State Minister of Cooperatives and Small and Medium Enterprises No 91/Kep/M. KUKM/IX/2004 concerning Guidelines for the Implementation of Service Cooperative Business Activities Sharia Finance, and Regulation of the State Minister for Cooperatives and Small and Medium Enterprises The purpose of this study is to find out about the implementation of financing and use qualitative methods knowing the solution path taken if BMT members do a problem The approach method used in this research is qualitative approach that conducts primary data research in the field. The juridical approach to researching regulations regarding the implementation of waqf and empirical not only as a set of rules, but as behavior in society The results of this study indicate that in the implementation of financing murabaha, BMT must be flexible with caution with 5C ratings on members who propose financing, preventive and preventive actions as well as kinship is prioritized in overcoming defaults committed by BMT customers. The judicial route can be one of the alternative solutions for defaults that occur carried out by customers and to protect assets from BMT and provide protection and legal certainty. Keywords : Mekanisme, Wakaf Uang BMT Abstrak: Abstrak memuat uraian singkat mengenai tujuan penulisan, metode yang digunakan, dan hasil penelitian (bila hasil dari penelitian). Abstrak berisi 200-300 kata. Abstrak ditulis dalam Bahasa Indonesia dan Bahasa Inggris. Pengetikan abstrak dilakukan dengan spasi tunggal dengan margin yang lebih sempit dari margin kanan dan kiri teks utama. Kata kunci perlu dicantumkan untuk menggambarkan ranah masalah yang diteliti dan istilah-istilah pokok yang mendasari pelaksanaan penelitian. Kata-kata kunci dapat berupa kata tunggal atau gabungan kata. Jumlah kata-kata kunci 3-5 kata. Kata-kata kunci ini diperlukan untuk komputerisasi. Pencarian judul penelitian dan abstraknya dipermudah dengan kata-kata kunci tersebut.